Unravelling the vital role of maxillofacial surgeons in paediatric oral and maxillofacial surgery: a case series - Nandimath, Santosh A.; G. C., Rajkumar; Patil, Kshitija; M., Mala (International Journal of Contemporary Pediatrics, 2024)
Oral and maxillofacial surgical procedures in children necessitate special considerations due to ongoing development. Key factors include obtaining parental consent, understanding developing anatomy and dentition, potential adverse effects on growth, behavioural guidance, and comprehensive peri- and postoperative care. This paper aims to outline the key considerations and challenges in managing paediatric oral and maxillofacial conditions. It seeks to review various treatment approaches for common conditions such as temporomandibular joint (TMJ) ankylosis, odontogenic cysts, tumours, maxillofacial trauma, and infections. Case studies are presented to illustrate various conditions and their management, reflecting contemporary practices and treatment strategies. The cases demonstrate diverse management approaches for paediatric oral and maxillofacial conditions. Dentigerous cysts and aggressive ossifying fibromas were treated with surgical interventions, including enucleation and reconstruction. TMJ ankylosis was addressed through aggressive resection and joint reconstruction, followed by intensive physiotherapy. Fractures and trauma cases were managed conservatively or with specialized techniques, such as botulinum toxin injections, highlighting the necessity for individualized treatment based on the specific injury and patient condition. Managing paediatric oral and maxillofacial conditions requires a tailored approach that balances effective treatment with the preservation of growth potential. Strategies must be adapted to accommodate the dynamic nature of growth and development in children, and regular follow-up is essential for monitoring outcomes and adjusting treatment plans as needed.